Hypoglycemia From a Cardiologist's Perspective - Sanon, Vani P. (Clin Cardiol, 2014)
Hypoglycemia in people with diabetes mellitus (DM) has been potentially linked to cardiovascular morbidity and mortality. Pathophysiologically, hypoglycemia triggers activation of the sympathoadrenal system, leading to an increase in counter‐regulatory hormones and, consequently, increased myocardial workload and oxygen demand. Additionally, hypoglycemia triggers proinflammatory and hematologic changes that provide the substrate for possible myocardial ischemia in the already‐diseased diabetic cardiovascular system. Hypoglycemia creates electrophysiologic alterations causing P‐R–interval shortening, ST‐segment depression, T‐wave flattening, reduction of T‐wave area, and QTc‐interval prolongation. Patients who experience hypoglycemia are at an increased risk of silent ischemia as well as QTc prolongation and consequent arrhythmias. The Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial showed an increase in all‐cause mortality with intensive glycemic control, whereas the Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified Release Controlled Evaluation (ADVANCE) study and Veteran's Affairs Diabetes Trial (VADT) showed no benefit with aggressive glycemic control. Women, elderly patients, and those with renal insufficiency are more vulnerable to hypoglycemic events. In fact, hypoglycemia is the most common metabolic complication experienced by older patients with DM in the United States. The concurrent use of medications like β‐blockers warrants caution in DM because they can mask warning signs of hypoglycemia. Here we aim to elucidate the pathophysiology, review the electrocardiographic changes, analyze the current clinical literature, and consider the safety considerations of hypoglycemia as it relates to the cardiovascular system. In conclusion, in the current era of DM and its vascular ramifications, hypoglycemia from a cardiologist's perspective deserves due attention.